The Effect Of Company Size, Industry Type And Research And Development Intensity On Intellectual Capital Disclosure - Ishaq; Riana Rachmawati Dewi; Anita Wijayanti (Journal of Economics, Business, and Government Challenges, 2020)
This study aims to determine the effect of company size, industry type, and the intensity of research and development on intellectual capital disclosure. This research uses secondary data in conducting analysis. The dependent variables are intellectual capital and independent variables, namely company size, industry type, research and development intensity. The population of this research is companies that are included in Kompas100 index on the IDX in 2018. The sample used in this study is 100 samples. Testing the hypothesis of this study using multiple linear regression test. The results showed that: 1) firm size had an effect on intellectual capital disclosure, 2) the type of industry had no effect on intellectual capital disclosure, 3) the intensity of research and development had no effect on intellectual capital disclosure.